A 1-day extreme rainfall event in Tasmania: process evaluation and long tail attribution - Tozer, CR; Risbey, JS; Grose, MR; Monselesan, DP; Squire, DT; Black, AS; Richardson, D; Sparrow, SN; Li, S; Wallom, D (American Meteorological Society, 2020)
Attribution of an extreme magnitude 1-day rainfall event in Hobart is inhibited by small sample size. For moderate magnitude Hobart daily rainfall extremes, models suggest that the associated extratropical lows will deliver more rainfall with weaker pressure anomalies in a warmer world.